The MIDAS dosimeter/particle monitor of charged particles and neutrons for space environment. (July 2020) - Lambropoulos, C.P.; Potiriadis, C.; Karafasoulis, K.; Papadimitropoulos, C.; Theodoratos, G.; Kazas, I.; Glikiotis, I.; Kοkavesis, Μ.; Dimopoulos, S.; Delakoura, A.; Pappas, S.; Loukas, D.; et al.
Abstract: Radiation doses received by astronauts outside the geomagnetic field are a main risk factor for human space exploration. The Miniaturized Detector for Application in Space (MIDAS) device is a highly miniaturized radiation detector (mass <50 g, volume < 5 × 5 × 1 cm 3 ) which is under development using fully depleted monolithic active pixel sensors and a plastic scintillator readout by a Silicon Photomultiplier. Its purpose is to measure dose and dose equivalent from both charged particles and fast neutrons. The device simulated response to galactic cosmic rays spectra has been treated with artificial intelligence techniques i.e. multi-classification for particle identification and regression for the determination of the kinetic energy of protons. Results indicate that particle identification and kinetic energy determination with the aid of these methods could be a viable approach. Highlights: Highly miniaturized energetic particles detector for space radiation. Machine learning for charged particle identification and kinetic energy determination. Space dosimetry.